하부 요로 증상 환자에서 교감 신경 활성도와 치료 효과와의 상관성 - Jang Hyun Ik (The Graduate School, Ajou University, 2015)
Purpose: In this study, we examined the difference in the treatment efficacy depending on the sympathetic activity in men with lower urinary tract symptoms (LUTS). Methods: In the current single-center, retrospective study, we evaluated a total of 66 male patients aged 40–70 years of age, pre¬senting with LUTS, whose International Prostate Symptom Score (IPSS) exceeded 8 points. They had a past 3-month history of taking alfuzosin XL, and their heart rate variability (HRV) was measured before and after the treatment. In addition, we also re¬cruited 39 healthy volunteers who visited a health promotion center for a regular medical check-up. They were aged between 40 and 70 years and had an IPSS of <8 points. We divided the patients with LUTS into two groups: the groups A and B, based on a low frequency/high frequency (LF/HF) ratio of 1.7, which was the mean value of the LF/HF ratio in the healthy volunteers. Af¬ter a 3-month treatment with alfuzosin XL, we compared treatment outcomes, based on the IPSS and peak urine flow rate, be¬tween the two groups. Results: A 3-month treatment with alfuzosin XL, comprising the measurement of the HRV, was performed for the 23 patients of the group A (23/38) and 17 of the group B (17/28). After a 3-month treatment with alfuzosin XL, total IPSS and IPSS ques-tionnaire 2 and 5 were significantly lower in the group A as compared with the group B. But this was not seen in the group B. Furthermore, there were no significant differences in other parameters, such as maximal flow rate and IPSS storage subscore, between the two groups. Conclusions: Our results indicate that the treatment efficacy was lower in patients with sympathetic hyperactivity as compared with those with sympathetic hypoactivity. Thus, our results will provide a basis for further studies to clarify causes of LUTS in a clinical setting.
학위논문(석사)--아주대학교 일반대학원 :의학과,2015. 2
Keywords: 자율신경계; 심박수; 하부 요로 증상